2018
DOI: 10.1186/s13068-018-1337-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism of phenol-tolerant Rhodococcus opacus strains for lignin bioconversion

Abstract: Background: Lignin is a recalcitrant aromatic polymer that is a potential feedstock for renewable fuel and chemical production. Rhodococcus opacus PD630 is a promising strain for the biological upgrading of lignin due to its ability to tolerate and utilize lignin-derived aromatic compounds. To enhance its aromatic tolerance, we recently applied adaptive evolution using phenol as a sole carbon source and characterized a phenol-adapted R. opacus strain (evol40) and the wild-type (WT) strain by whole genome and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…Since lignocellulosic degradation products are mixtures of compounds, R. opacus's co-utilization patterns will help to develop predictive metabolic models as well as guide future metabolic engineering efforts toward more-efficient conversion of lignocellulose to biofuels and biochemicals. Combining our findings from this work with our previous reports (Hollinshead et al, 2015;Henson et al, 2018a;Henson et al, 2018b, Yoneda et al, 2016, we are developing a genome-scale metabolic model that enables prediction of metabolic fluxes for diverse carbon sources. Quantitative flux profiles obtained through 13 C-MFA provide an accurate description of internal metabolism that is invaluable when deciding future metabolic engineering approaches.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Since lignocellulosic degradation products are mixtures of compounds, R. opacus's co-utilization patterns will help to develop predictive metabolic models as well as guide future metabolic engineering efforts toward more-efficient conversion of lignocellulose to biofuels and biochemicals. Combining our findings from this work with our previous reports (Hollinshead et al, 2015;Henson et al, 2018a;Henson et al, 2018b, Yoneda et al, 2016, we are developing a genome-scale metabolic model that enables prediction of metabolic fluxes for diverse carbon sources. Quantitative flux profiles obtained through 13 C-MFA provide an accurate description of internal metabolism that is invaluable when deciding future metabolic engineering approaches.…”
Section: Discussionmentioning
confidence: 77%
“…Isolated from a gas works plant, this strain is capable of accumulating triacylglycerol (TAG), the precursor for biodiesel up to 80% of its dry cell weight (Alvarez et al, 1996). Studies of its mechanisms of aromatic tolerance and TAG accumulation have found promising results for its use in the conversion of lignin-derived aromatic substrates (DeLorenzo et al, 2017;Henson et al, 2018a;Henson et al, 2018b;Yoneda et al, 2016). R. opacus has been extensively studied for its growth kinetics and transcriptional activities, yet key knowledge gaps from genotype to phenotype still remain.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, R. opacus, the other Gram-positive species in our collection, did not show any obvious signs of substrate inhibition (Fig. 3h), likely because it has an unusually complex mycolic-acid envelope which has been associated with phenol tolerance and even enables growth on phenol as a sole carbon source [83].…”
Section: Promising Species For Industrial Production Of Fuels and Chementioning
confidence: 87%
“…Lipids are one of the few groups of complex organic substances for which the composition can be adequately regulated by the bacterial cell in response to suboptimal growth conditions by changing the structure and relative amount of membrane fatty acids [ 116 ]. The key role in determining the fluidity and permeability of Rhodococcus cell membranes is due to the composition of fatty acids, which can vary in the length and degree of saturation of the hydrocarbon chains depending on the organic substrate consumed [ 29 , 117 , 118 , 119 ].…”
Section: Adaptive Cell Modifications Of Rhodococci Exposed To Hydrocarbons and Other Environmental Pollutantsmentioning
confidence: 99%